PENGARUH PRESTASI AKADEMIK, LITERASI BISNIS, DAN GAYA HIDUP TERHADAP INTENSI MAHASISWA BERWIRAUSAHA - Rahayu Mardikaningsih; Didit Darmawan (Jurnal Ilmiah Satyagraha, 2023)
Carrying out exploration based on the influence of academic achievement, business literacy and lifestyle on student intentions to become entrepreneurs is the goal of this research. The students who are the sample are students in the city of Surabaya who are studying at private universities and of course have taken entrepreneurship courses. The technique for taking the sample is accidental. The data analysis will utilize a technique called multiple regression. Data was collected through the use of a questionnaire which included the variables of academic achievement, business literacy, lifestyle and entrepreneurial intentions. The effect of the independent variable on the dependent variable can be evaluated on the basis of multiple regression analysis. Based on the results of his research, several factors that shape student entrepreneurial intentions can be better understood. These findings can be a reference for universities and educational institutions in developing more effective entrepreneurship programs. It is hoped that in the future the number of students interested in becoming entrepreneurs will increase even more because the relationship between academic achievement, business literacy, lifestyle, and entrepreneurial intentions has been well understood.